234 Pregnancy and Hormonal Response in Suckled Beef Cows Administered High-concentration Prostaglandin F2α in a 5-day CO-Synch + CIDR Synchronization Program. (8th October 2021) - Ahmadzadeh, Amin; Corpron, McKenzie; Hall, John B; Ahmadzadeh, Amin; Dalton, Joe
Abstract: Two injections of prostaglandin F2 (PGF) in a 5-d CO-Synch+CIDR timed-AI protocol (5-d CIDR) is necessary to induce luteolysis and reduce serum progesterone (P4) concentrations by the time of AI in beef cattle. The objectives were to examine the effects of a single high-concentration dose of PGF in a 5-d CIDR protocol on P4 concentration and pregnancy per AI (P/AI) beef cows. Angus-Hereford cows (n = 404) were synchronized (d0) with a 5-d CIDR protocol and assigned to receive either one injection of high-concentration PGF on d5 (HC; total dose: 25 mg; n = 203) or two injections of conventional PGF (2PG; each injection: 25 mg; n = 201), at CIDR removal (d5) and 8 h later. All cows received AI at a fixed time 72 h after PGF treatment (d8). Pregnancy was determined by ultrasound 48–63 days after AI. For P4 and cyclicity determination, blood samples were collected on d -7, 0, and 8. Cyclicity status and proportion of cows with a CL at d0 did not differ between treatments. Proportion of cows detected in estrus was greater (P = 0.01) for 2PG (63.1%) than HC (49.3%). Treatment did not affect P/AI (P = 0.87; 51% vs. 52% for HC and 2PG, respectively). Serum P4 at AI also affected (P < 0.01) P/AI; as P4 concentration increased, P/AI decreased. ROC analysis showed a greater P/ AI when P4 was < 0.43 ng/mL. Fewer (P < 0.01) HC cows had P4 < 0.43 ng/mL at AI than 2PG (84.0 and 97.0%, respectively). Nonetheless, mean P4 concentrations at AI were less than 0.4 ng/mL for HC and 2PG. Although two doses of conventional PGF (total dose: 50 mg) more effectively reduced P4 to < 0.43 ng/mL by the time of AI than one dose of high-concentration PGF (total dose: 25 mg), P/AI was not different between treatments.